Hubungan komunikasi interpersonal dengan kepuasan kerja pegawai di Dinas Pendidikan Kota Padang - Fitra Maya Maya; Nelitawati Nelitawati; Ahmad Sabandi; Nelfia Adi (Universitas Negeri Padang, 2021)
The purpose of this research is to obtain information about the relationship between interpersonal communication and job satisfaction of employees at the Padang City Education Office from the point of view of openness, empathy, support, equality, and positive attitudes (variable X) and likes to work, enthusiastic at work, and not. protest at work (variable Y). All employees of Padang City Education Office are the population in this study, amounting to 117 people with a sample of 54 employees. The instrument uses a Likert scale questionnaire which has been tested to observe the validity and reliability of the questionnaire. This data is analyzed using the mean (average) formula. The results of this research are the relationship between interpersonal communication and job satisfaction of employees at Padang City Education Office seen from the value (1) like to work with a score of 31.3 (2) enthusiastic at work with a score of 62.2 (3) do not protest at work with a score of 30 , 8 (variable Y) and (1) openness with a score of 22.18 (2) empathy with a score of 22.44 (3) support with a score of 26.16 (4) similarity with a score of 30.1 (5) a positive attitude with a score 27.1 (variable X). The conclusion is that there is no relationship between interpersonal communication and job satisfaction of employees at Padang City Education Office.